Higher titers of anti‐Chlamydia pneumoniae IgG in diabetic retinopathy: a cross‐sectional study. Issue 2 (14th September 2014) - Banaee, Touka; Daneshvar Kakhki, Ramin; Abrishami, Mojtaba; Mahmoudi, Mahmoud; Farzadnia, Mehdi
Abstract Background Chronic inflammation has a role in the pathogenesis of diabetic retinopathy. Infection with intracellular organisms may incite chronic inflammation. This study was conducted to investigate the association between previous infection with Chlamydia pneumoniae (an intracellular microorganism) and diabetic retinopathy. Methods Patients with type 2 diabetes mellitus (30–60 years old) and age‐matched normal controls were recruited. Patients with history of cardiovascular or cerebrovascular disease, recent pulmonary infection and the presence of age‐related macular degeneration were excluded from the study. Complete ophthalmic examinations were performed. Fasting blood sugar and haemoglobin levels were measured in diabetic patients and controls, and HgbA1c, blood urea nitrogen, creatinine and 24‐h urine protein were measured in diabetic patients. Anti‐C. pneumoniae IgG (enzyme‐linked immunosorbent assay) was measured in the sera of all participants. Results A total of 215 type 2 diabetic patients and 243 normal healthy controls were included. Anti‐C. pneumoniae IgG titers were higher in patients affected by diabetic retinopathy than participants without retinopathy (74.78 ± 33.38 vs 66.18 ± 31.40, p = 0.028). Diabetic patients with diabetic retinopathy also had higher titers than diabetic patients without diabetic retinopathy (74.78 ± 33.38 vs 66.11 ± 33.41, p = 0.042). Of different variables including age, body mass index, haemoglobin level, glycated haemoglobin level, fasting blood sugar, mean arterial pressure and blood urea nitrogen, only age (r = 0.17; p = 0.001) and body mass index (r = 0.15; p = 0.003) were correlated with anti‐C. pneumoniae IgG levels. In regression analysis, the presence of diabetic retinopathy was still a determinant of the antibody level (p = 0.03). Conclusion Anti‐C. pneumoniae IgG titers were higher in patients with diabetic retinopathy, which may indicate a role of this infection in the pathogenesis of diabetic retinopathy. Copyright © 2014 John Wiley & Sons, Ltd.